How Consistent are Perinatal Case Disease Diagnosis Codes Based on ICD 10? A Case Study from Ciremai Hospital - Budiyanti, Nita; Nur Afika, Siti; Ernawati, Nunung; Nurulramdhini, Citra (Jurnal Medisci, 2023)
The mortality rate of neonatal cases in Indonesia in 2021 reached 20,154 cases, the cause of death was dominated by diagnoses of Low Birth Weight, asphyxia, infections, and congenital abnormalities. In health care practice, the diagnosis of illness during treatment will be recorded in a medical record. The medical record will contain administrative and clinical data, one of which contains the diagnosis code and actions during treatment. The diagnosis code established in the medical record must be precise, accurate, and consistent in accordance with ICD-10. This study included a type of quantitative descriptive research with a sample of 222 infant medical records, the sample technique used was purposive sampling. The results showed that the coding process at Ciremai Hospital in Cirebon City was 100% electronic, where from 222 infant medical record documents there were 167 consistent diagnosis codes and 55 inconsistent diagnosis codes. This is caused by 2 things, namely improper diagnosis codes and improper code reselection. Thus, the determination of the diagnosis code for perinatal cases at Ciremai Hospital in Cirebon City in 2022 shows that the consistency of the diagnosis code of 75% or as many as 167 diagnosis codes is consistent.